(untitled) (Clinics, 2012)
OBJECTIVE: Human diploid fibroblasts undergo a limited number of cellular divisions in culture and progressively reach a state of irreversible growth arrest, a process termed cellular aging. The beneficial effects of vitamin E in aging have been established, but studies to determine the mechanisms of these effects are ongoing. This study determined the molecular mechanism of γ-tocotrienol, a vitamin E homolog, in the prevention of cellular aging in human diploid fibroblasts using the expression of senescence-associated genes. METHODS: Primary cultures of young, pre-senescent, and senescent fibroblast cells were incubated with γ-tocotrienol for 24 h. The expression levels of ELN, COL1A1, MMP1, CCND1, RB1, and IL6 genes were determined using the quantitative real-time polymerase chain reaction. Cell cycle profiles were determined using a FACSCalibur Flow Cytometer. RESULTS: The cell cycle was arrested in the G0/G1 phase, and the percentage of cells in S phase decreased with senescence. CCND1, RB1, MMP1, and IL6 were upregulated in senescent fibroblasts. A similar upregulation was not observed in young cells. Incubation with γ-tocotrienol decreased CCND1 and RB1 expression in senescent fibroblasts, decreased cell populations in the G0/G1 phase and increased cell populations in the G2/M phase. γ-Tocotrienol treatment also upregulated ELN and COL1A1 and downregulated MMP1 and IL6 expression in young and senescent fibroblasts. CONCLUSION: γ-Tocotrienol prevented cellular aging in human diploid fibroblasts, which was indicated by the modulation of the cell cycle profile and senescence-associated gene expression.